Torture porn : popular horror after Saw - Jones, Steve (Houndmills, Basingstoke : Palgrave Macmillan, 2013)
Lambasted by critics as a sign of censorial failure and even social decline, the horror subgenre known as 'torture porn' has generated a great deal of controversy during the last decade. Although torture porn films such as Saw, Hostel and The Human Centipede were highly successful and have become cultural touchstones, the term 'torture porn' remains synonymous with misogyny, obscenity and morally depravity. Arguing primarily in defense of these popular torture-themed horror films, this is the first book to offer a detailed critical examination of the 'torture porn' phenomenon, outlining the subgenre's lineage, scrutinizing responses to the sub-genre, and offering narrative analyses of the sub-genre's central box-office hits as well as the multitude of independent direct-to-DVD films that have followed in their footsteps. In doing so, this book seeks to unpick the relationships between 'porn', 'horror', 'immorality', and 'extremity'.
Introduction: 'Welcome to your worst nightmare' -- Part I: 'Torture porn' (Category) -- 1. 'The past catches up to everyone': Lineage and nostalgia -- 2. 'Bend to our objectives': 'Torture Porn' as press discourse -- 3. 'No-one approves of what you're doing': Fans and filmmakers -- Part II: 'Torture' (Morality) -- Introduction -- 4. 'Your story's real, and people feel that': Contextualising torture -- 5. 'Some are victims. Some are predators. Some are both': Torturous positions -- 6. 'In the land of the pig, the butcher is king': Torture, spaces, and power -- Part III: 'Porn' (Extremity) -- Introduction -- 7. 'Ladies first'?: Torture porn, sex, and misogyny -- 8. 'Why are you crying? Aren't you having fun?': Extreme porn -- 9. 'You will not believe your eyes...or stomach': Hardcore horror -- Conclusion: 'Will you continue?': Beyond 'Torture porn'.
Bibliografija: str. 202-216.
Filmografija.
Kazalo.
Keywords: Horor filmovi; Filmovi strave; Mučenje na filmu